2015
DOI: 10.1097/dss.0000000000000291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Second Injection of Botulinum Toxin on Lower Facial Contouring, as Evaluated Using 3-Dimensional Laser Scanning

Abstract: The administration of a second BoNT-A injection is effective for better aesthetic results for the lower facial contour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…This means that additional injection of BoNT-A is required to sustain its effect in the lower facial contour. In the present study, we found that repeated injections of BoNT-A induced a greater reduction of masseter muscle thickness and cross-sectional area than did a single injection, as reported by Lee et al18 This indicates that repeated injections of BoNT-A were more effective in improving masseteric hypertrophy, and suggests that repeated injections might induce more bony changes.…”
Section: Discussionsupporting
confidence: 89%
“…This means that additional injection of BoNT-A is required to sustain its effect in the lower facial contour. In the present study, we found that repeated injections of BoNT-A induced a greater reduction of masseter muscle thickness and cross-sectional area than did a single injection, as reported by Lee et al18 This indicates that repeated injections of BoNT-A were more effective in improving masseteric hypertrophy, and suggests that repeated injections might induce more bony changes.…”
Section: Discussionsupporting
confidence: 89%
“…75,76 The same is also true on an inter-patient basis. In a comparison of onset and duration of effect in the glabellar region with ABO, ONA, and INCO, Rappl et al noted that subjects with the longest duration of response had mild wrinkles at baseline and very thin corrugator muscles.…”
Section: The Influence Of Muscle Mass On Abo Efficacymentioning
confidence: 65%
“…Perhaps owing to the low incidence rate, reports on the complications of toxin injections for masseter hypertrophy remain rare or even unobserved in certain studies despite the treatment's popularity. 1,[15][16][17][18][19][20][21][22][23][24][25][26][27] Current literature does not offer comprehensive reviews of the time, prognosis, or recovery process of related complications, and the Cochrane review in 2009 and 2013 reported an insufficient amount of high level evidence to accurately assess the efficacy and safety of toxin injections for masseter hypertrophy. 28,29 A previous report by the authors in 2018 outlined masseter toxin injection complication rates from 2036 treatments, 30 though it was limited in scope to a single clinic.…”
mentioning
confidence: 99%